Biodiversity of beet webworm microsporidia in Eurasia - Malysh Julia; Tokarev Yuri; Malysh Svetlana; Xingfu Jiang; Frolov Andrei (BIO Web of Conferences, 2020)
The beet webworm Loxostege sticticalis (LS) has eruptive type of population dynamics and high migratory activity. The LS outbreaks are therefore difficult to predict and the pest belongs to the category of highly dangerous pests. However, during periods of depressions this insect is not observed within the most of its range and is very susceptible to infection by pathogens, including various species of microsporidia, some of which are not specific parasites of the order Lepidoptera. The distribution of LS microsporidia in Eurasia is quite extensive. During the study period of LS from 2003 to 2019, we have found 6 species of microsporidia. The parasite list includes not only species known for Lepidoptera such as Nosema sp. and Vairimorpha thomsoni, but also Vairimorpha (Nosema) ceranae as the typical pathogen from Apis mellifera, as well as Endoreticulatus cf poecilimonae, a pathogen similar to Endoreticulatus poecilimonae from Poecilimon thoracicus. Moreover, two isolates from the genus Tubulinosema identified in LS belong to the group of parasites with a very wide host range, including humans. In laboratory experiments, LS proved high sensitivity to microsporidia N. pyrausta from Ostrinia nubilalis and N. tyriae from Tyria jacobaeae. Its susceptibility to Paranosema locustae from Locusta migratoria has also been discovered.